Training in The Identification and Handling of Students with Special Needs using The Assessment Application at Pondok Nasyrul Ulum Aengdake Bluto District: Pelatihan Identifikasi dan Penanganan Siswa Berkebutuhan Khusus Menggunakan Aplikasi Asesmen Di Pondok Pesantren Nasyrul Ulum Aengdake Kecamatan Bluto - Choli Astutik; Tri Sukitman; Yeni Puji Astuti; M. Ridwan; Kurratul Aini (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The purpose of carrying out this community service activity was based on findings about problems experienced by Nasyrul Ulum, an Islamic Boarding School in Aengdake Bluto District. The problems were : a). Some teachers and partners of Nasyrul Ulum Islamic Boarding School found difficulties in understanding the students' characteristics and the progress of those with special needs. The proposing team offered to provide solutions on understanding and increasing knowledge related on it. 2). Increasing skills for teachers to easily identify the students with special needs and its category as well. The activity, in terms of identifying and handling students with special needs, was held on September to November 2021 in Nasyrul Ulum auditorium. The training included; preparation, main activity, and post activity. The conclusion were; a). The training on identifying students with special needs in Nasyrul Ulum Islamic Boarding School ran well, b). The training on identifying students with special needs in Nasyrul Ulum Islamic Boarding School enthusiastically responded by students of Elementary and Junior High School in Aengdake Bluto District, and c) The participants of the training understood to identify the students with special needs, and to operate its application.